Cultural Transmission of Traditional Knowledge in two populations of North-western Patagonia - Lozada Mariana; Ladio Ana H; Eyssartier Cecilia (BMC, 2008)
Abstract Background In the present study we have investigated the cultural transmission of two types of traditional plant knowledge in two communities of North-western Patagonia, Argentina. In the Pilcaniyeu community, we studied the transmission of traditional knowledge related to horticultural practices in home-gardens, greenhouses and gardens; while in the community of Cuyin Manzano, we studied wild plant gathering customs. Methods Ethnobotanical fieldwork was conducted by means of semi-structured interviews, in which we investigated which plants are used, at what life history phase was learned, modes of transmission and who the principal transmitters were in childhood and adulthood. In both communities, each of this three aspects related to cultural transmission were categorized and the frequencies of each category were obtained. The total number of species recorded in each community was also calculated. Frequencies were analyzed with the Chi-square test of independence. Results and discussion In both communities, transmission of traditional plant knowledge begins at an early age, as a family custom, in which women play a predominant role. Wild plant use and horticultural knowledge continue to be learned during adulthood. This was particularly registered associated with horticultural learning, which receives greater influence from extension agents who are introducing new practices and technology. This outside influence, which implies novelty, could imply syncretism but also traditional knowledge loss. Conclusion Given the remarkable acculturation processes occurring at present in rural communities of Northwestern Patagonia, it might be of vital importance to document traditional knowledge of ancient practices. Moreover, it could be interesting to share our results with both populations in order to encourage participatory activities within the communities which could enhance traditional knowledge horizontal transmission, particularly among elder adults and youngsters.